Local Generation of High‐Frequency Plasmaspheric Hiss Observed by Van Allen Probes - Zhaoguo He; Lunjin Chen; Xu Liu; Hui Zhu; Si Liu; Zhonglei Gao; Yong Cao (Geophysical Research Letters)
Abstract The generation of a high‐frequency plasmaspheric hiss (HFPH) wave observed by Van Allen Probes is studied in this letter for the first time. The wave has a moderate power spectral density (∼10−6 nT2/Hz), with a frequency range extended from 2 to 10 kHz. The correlated observations of waves and particles indicate that HFPH is associated with the enhancement of electron flux during the substorm on 6 January 2014. Calculations of the wave linear growth rate driven by the fitted electron phase space density show that the electron distribution after the substorm onset is efficient for the HFPH generation. The energy of the contributing electrons is about 1–2 keV, which is consistent with the observation. These results support that the observed HFPH is likely to be generated locally inside the plasmasphere due to the instability of injected kiloelectron volt electrons.